Magnetization of High Temperature Superconducting Trapped-Field Magnets - Zou, Shengnan (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2017)
High temperature superconducting (HTS) bulks and stacks of coated conductors can be magnetized to become trapped-field magnets that provide much stronger magnetic fields than those reachable with conventional permanent magnets. This work investigates the flux dynamics during the magnetization of HTS trapped-field magnets and proposes possible strategies to improve the trapped field produced by the pulsed field magnetization method that is promising for practical applications.